Sexual violence as political violence in the dictatorships of Argentina and Chile - Poblete-Hernández, Nadia (2024)
Forty years after the beginning of the transition in Argentina and 50 years after the Chilean coup d'état, this article analyzes the sexual violence against women implemented in clandestine detention centers (CDCs) as political, terrorist, and genocidal violence. Through a qualitative approach to the testimonies of former political prisoners, this paper aims to understand sexual violence against women in the experiences of concentration camps as a specific form of violence within the framework of conservative reconstructions of the civil-military dictatorships in Argentina and Chile. This violence, which was a total patriarchal act, not only sought to punish and discipline “deviant” female militants, but also to harm militant men. Likewise, it was established as a permanent threat against female detainees and a way of suppressing change and subjective, cultural, and social subversions, which, in parallel or as part of the political experience, developed in the countries of the Latin American Southern Cone. It is argued that sexual violence is a form of terrorism and genocide, since it projects terror into a specific group of the population and seeks to annul the possibility of being a woman when she breaks with the sacralized mandates of the patriarchal order.